2010
DOI: 10.1016/j.immuni.2010.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Autoimmunity by Boosting Memory-like Autoregulatory T Cells

Abstract: Blunting autoreactivity without compromising immunity remains an elusive goal in the treatment of autoimmunity. We show that progression to autoimmune diabetes results in the conversion of naive low-avidity autoreactive CD8(+) T cells into memory-like autoregulatory cells that can be expanded in vivo with nanoparticles coated with disease-relevant peptide-major histocompatibility complexes (pMHC-NP). Treatment of NOD mice with monospecific pMHC-NPs expanded cognate autoregulatory T cells, suppressed the recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
320
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 284 publications
(332 citation statements)
references
References 35 publications
11
320
1
Order By: Relevance
“…7 The finding that insulin-secreting cells could fully recover under conditions that restrain their devastation inspired exploration of the immunomodulatory approaches for therapy of T1D. [8][9][10][11][12][13][14] To further explore the concept that suppression of autoimmunity could become an adequate condition for recovery of the autologous insulin-secreting tissue, we established a model in which recovery of the physiological function of the autologous b cells was achieved in nonobese diabetic (NOD) mice by induction of allogeneic hemopoietic chimerism after the onset of hyperglycemia. The therapeutic regimen utilized in this model consisted of transplantation of allogeneic bone marrow (BM) in combination with the islets of Langerhans, which were MHC-matched to the donor's BM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The finding that insulin-secreting cells could fully recover under conditions that restrain their devastation inspired exploration of the immunomodulatory approaches for therapy of T1D. [8][9][10][11][12][13][14] To further explore the concept that suppression of autoimmunity could become an adequate condition for recovery of the autologous insulin-secreting tissue, we established a model in which recovery of the physiological function of the autologous b cells was achieved in nonobese diabetic (NOD) mice by induction of allogeneic hemopoietic chimerism after the onset of hyperglycemia. The therapeutic regimen utilized in this model consisted of transplantation of allogeneic bone marrow (BM) in combination with the islets of Langerhans, which were MHC-matched to the donor's BM.…”
Section: Introductionmentioning
confidence: 99%
“…This observation supports our conclusions that: (i) the lack of the Treg cells and the impaired function of the CXCR4/SDF-1 axis in the PLNs of the NOD mice may play a role in diabetogenesis; and (ii) that an improved Treg cell accumulation in the PLNs reflects recovery of the peripheral tolerance in the PLNs of the antea-diabetic NOD mice and is part of the mechanisms leading to the resumption of euglycemia in these animals. In light of the recent finding that full regeneration of the b cells to their physiologic capacity could be achieved in the murine model of T1D after the onset of hyperglycemia, [8][9][10][11][12][13]18 immunomodulatory protocols aiming at promoting Treg cell retention in the PLNs can be considered possible means for induction of a condition favoring b cell regeneration in T1D.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that CD8 + T cells specific for peptide epitopes derived from autoantigens expressed by islet cells can be differentiated into regulatory T cells (Tsai et al 2010). Immunization of NOD mice transgenic for a TCR derived from a diabetogenic CD8 + T cell, specific for an IGRP peptide, led to the differentiation of CD8 + T cells with an autoregulatory phenotype (Tsai et al 2010).…”
Section: Cytotoxic Cd8 T Lympochytes: Are They Regulatory?mentioning
confidence: 99%
“…Immunization of NOD mice transgenic for a TCR derived from a diabetogenic CD8 + T cell, specific for an IGRP peptide, led to the differentiation of CD8 + T cells with an autoregulatory phenotype (Tsai et al 2010). These memory-like autoregulatory T cells not only prevented the development of T1D in prediabetic animals, but also restored normoglycemia in diabetic animals.…”
Section: Cytotoxic Cd8 T Lympochytes: Are They Regulatory?mentioning
confidence: 99%
See 1 more Smart Citation